Judging psycholegal reporting in civil court proceedings in the Eastern Cape - Marais, Claire Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
Purpose: The primary purpose for this research was to evaluate the quality of psycholegal reports, and the qualification of the authors. Previous research had revealed generalised poor practices in psycholegal report writing and the authors seemed unqualified as expert witness. This negatively influenced the impression and usefulness of expert psychological opinion in South African courts. The secondary purpose was to compare the results to those determined by Ireland (2012), which was a useful benchmark study in the UK as her findings corresponded with the literature. Method: This archival research analysed a hand-search sample of 20 reports written by 20 psychologists based nationally. These reports were submitted as expert opinion in civil proceedings in the Grahamstown Division of the Eastern Cape High Court between 2011 and 2016. Ireland and Pinschof's (2009) measure 'Quality Rating Scale' was adapted for a South African context and used to evaluate quantitatively the reports. Focus was on the reports' contents (fact and opinion), methods, process and overall rating, and the qualification of the authors. Results: Overall, two-thirds of the reports were rated as 'good' and 'very good'. The results were generally more positive than Ireland's (2012) findings. However, there were practices in the report writing that were deemed detrimental to the quality of the expert's opinion. This included vague referral questions and unclear basis for concluding opinions and diagnosis. There was also a lack of discussions surrounding the scientific trustworthiness of testing methods and absent ethical considerations. Lastly, the specialised expertise of the experts was not adequately documented. Conclusion: The findings painted a more positive picture of psycholegal reporting in South Africa than illustrated in previous research, which seemingly relied on anecdotes and subjective surveys. This study used a systematic and objective measure. The findings of this study, previous research and ethical Rules of Conduct were used to consider recommendations for psycholegal report writing, and the improvement of the field of psycholegal work. Lastly, the focus of future research was discussed.
Keywords: Court proceedings -- South Africa -- Eastern Cape; Evidence, Expert -- South Africa -- Eastern Cape; Forensic psychology -- South Africa -- Eastern Cape; Quality Rating Scale (QRS); Psycholegal reporting -- South Africa -- Eastern Cape